77.2k views
3 votes
Solve the equation for x.



-7(x - 2) + 5(3 - x) = 4x - 3

User Ray Hulha
by
5.5k points

2 Answers

5 votes

Answer: x=2

Explanation:

Simplify the equation

-12+29= 4x-3

Subtract 29 from both sides

12x=4x-32

Subtract 4x from both sides (Simplify)

-16x=-32

Divide both sides by -16

x=2

User Ahmed Abdelkader
by
5.0k points
2 votes

Answer:

x=2

Explanation:

-7x+14+15-5x=4x-3

-12x+29=4x-3

-12x-4x=-29-3

-16x=-32

x=-32/-16

x=2

User Rome
by
5.2k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.